Preparing Teachers for a ChatGPT-Influenced Workforce - Helvacı, İsmail (Kastamonu Egitim Dergisi, 2025)
Purpose: In the 21st century, unique changes have become apparent in our lives. These changes have affected numerous fields, and education is no exception. Innovations in education have progressed rapidly, particularly with the prevalence of Artificial Intelligence (AI) applications. Higher education institutions play a crucial role in these developments due to their capacity to shape professional competencies and raise societal awareness. This study discusses the impact of AI applications on higher education and their significance in teacher training. Design/Methodology/Approach: The study explores AI applications in higher education, particularly in preparing prospective teachers for AI-driven work environments. A review of literature and current educational practices was conducted to assess the integration of AI into teacher training programs. The study focuses on AI literacy, curriculum adaptation, and professional development. Findings: AI applications have started to transform higher education by enhancing pedagogical methods, improving access to educational resources, and redefining the skill sets required for future educators. However, there remains a gap in AI literacy among pre-service teachers. Higher education institutions must incorporate AI-based courses and digital competencies to prepare teachers effectively. Highlights: The study emphasizes the need for AI literacy in teacher training programs to ensure future educators can effectively utilize AI technologies in their profession. Recommendations include updating curricula, integrating AI-driven tools, and fostering interdisciplinary collaboration in higher education.